Industrial work placement in higher education: A study of civil engineering student engagement. Issue 2 (April 2018) - Tennant, Stuart; Murray, Mike; Gilmour, Bob; Brown, Linda
For civil engineering undergraduates, short-term industrial work placement provides an invaluable learning experience. Notwithstanding the near-universal endorsement of short-term placement programmes, the resulting experience is rarely articulated through the student voice. This article provides an analysis of 174 questionnaires returned by placement undergraduates studying civil engineering at four higher education institutions in the West of Scotland. The commentary captures industrial placement statistics, employability skill sets and a preliminary semantic interpretation of participants' testimonies. While the student journey to becoming a professional civil engineer is undoubtedly enhanced by short-term industrial placement, the findings disclose opportunities for university and industry to challenge and affect pedagogical discourse in relation to personal and professional development. The discussion is likely to resonate beyond civil engineering and may serve as a timely reminder of the necessity of periodically revisiting and reinvigorating academia–industry curriculum partnerships.